Desire, indefinite lifespan, and transgenerational brains in literature and film. (October 2016) - Vidal, Fernando
Even before the brain's deterioration became a health problem of pandemic proportions, literature and film rehearsed the fiction of brain transplantations that would allow an aging person to inhabit a younger body, so that successive surgeries may result in that person's immortality. Such fiction makes the brain operate like an immaterial soul that does not undergo physical decline. This article examines that fiction as elaborated in Hanif Kureishi's The Body and several films in connection with older fantasies that articulate desire, eternal youth, and personal immortality, with philosophical discussions about brain and personhood, and with people's assimilation of neuroscientific idioms into their views and practices of personal identity. In conclusion it discusses how, in contrast to philosophical approaches that tend to focus on self-consciousness, first-person perspectives, and individual autonomy, fiction may contribute to direct attention to relationality as constitutive of personhood.